2002
DOI: 10.1002/jrs.867
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of mono‐oxo and polyoxo and of monomeric and polymeric vanadate, molybdate and tungstate species in metal oxide catalysts by IR and Raman spectroscopy

Abstract: The expected and experimental features of vanadate, molybdate and tungstate species observed in inorganic compounds of different structures are discussed. In particular, fourfold coordinated species (truly tetrahedral and distorted tetrahedral), isolated and polymeric mono-oxo and dioxo metallyl species are discussed. On these bases, some of the data concerning surface species in oxide-supported oxides are also considered. The need to perform both IR and Raman experiments and, if possible, O-18/O-16 exchange e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
161
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(177 citation statements)
references
References 68 publications
16
161
0
Order By: Relevance
“…At dehydrated conditions and low loadingsbelow the monomeric monolayer (2.3 VO x /nm 2 ) as defined by Khodakov 7 sthe vanadium oxide species on the surface will be present only as a monomeric VO 4 cluster with one VdO bond. 17,18 EXAFS data analysis showed that for all supports the VO 4 cluster is attached to the surface with only one V-O b -M support bond under the applied measurement conditions. Both the V-O b bond distance and the V‚‚‚ M support distance depend on the structure of the support surface.…”
Section: Introductionmentioning
confidence: 94%
“…At dehydrated conditions and low loadingsbelow the monomeric monolayer (2.3 VO x /nm 2 ) as defined by Khodakov 7 sthe vanadium oxide species on the surface will be present only as a monomeric VO 4 cluster with one VdO bond. 17,18 EXAFS data analysis showed that for all supports the VO 4 cluster is attached to the surface with only one V-O b -M support bond under the applied measurement conditions. Both the V-O b bond distance and the V‚‚‚ M support distance depend on the structure of the support surface.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, other species (d) and (e) are proposed to be formed under various measurement conditions. The di-oxo structure (a) is commonly rejected based on the results of EXAFS analysis [30][31][32][33] and the absence of a symmetric and anti-symmetric V O stretching band in the vibrational spectra [59][60][61]. The single V O nature of the VO 4 unit has been confirmed with 18 O labeling experiments in conjunction with Raman spectroscopic analysis [60,61].…”
Section: Introductionmentioning
confidence: 99%
“…The intensities of the absorption in the OH region in the spectra of the ion-exchanged samples parallel the intensities of the W=O bands. This indicates that the OH coverage of the activated samples is associated with hydroxyls produced by dissociative adsorption of ambient water on coordinatively unsaturated (cus) W=O groups [38]. The OH groups complete the coordination sphere of the W=O species and give rise to Brønsted acid sites [38].…”
Section: In Situ Ft-ir Spectroscopymentioning
confidence: 99%
“…This indicates that the OH coverage of the activated samples is associated with hydroxyls produced by dissociative adsorption of ambient water on coordinatively unsaturated (cus) W=O groups [38]. The OH groups complete the coordination sphere of the W=O species and give rise to Brønsted acid sites [38]. Since the number of the cus W=O species decreases with the increase in the W coverage, the amount of the W-OH groups decreases as well.…”
Section: In Situ Ft-ir Spectroscopymentioning
confidence: 99%